DASAR PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA - Rafael Sianipar (Jetri : Jurnal Ilmiah Teknik Elektro, 2014)
Solar energy as a source of primary energy is a renewable energy. It is available abundantly in Indonesia. One of the technological utilization of solar energy into electrical energy is the use of photovoltaic or solar modules, called Photovoltaic Power Plant or PLTS. At present, the utilization of solar energy for power generation sources is growing rapidly in a wide range of power scaling. However, there is no standard was established in Indonesia in connection with the construction of photovoltaic power generation. Photovoltaic power plant currently purposed to speed up electrification ratio and reduce the consumption of fuel in remote area, which generally scale power plants below 1 MW. PLN as State Owned Electricity Company is responsible in raising the electrification ratio needs a technical standard that can be used by region office in planning and building a PLTS. This paper describes the base-configuration of photovoltaic system, important technical specifications of main equipment such as solar modules, inverters and batteries, the consideration to choose the capacity is also included. Keywords: solar energy, photovoltaic, base-configuration, deep cycleEnergi surya merupakan sumber energi terbarukan yang tersedia secara berlimpah di Indonesia. Salah satu cara memanfaatkan energi surya adalah dengan mengubahnya menjadi energi listrik menggunakan modul fotovoltaik atau modul surya yang disebut pembangkit listrik tenaga surya (PLTS). Dewasa ini pemanfaatan energi surya sebagai pembangkit tenaga listrik berkembang pesat, akan tetapi belum ada standard terkait pembangunan PLTS di Indonesia. Pembangunan PLTS dapat mempercepat rasio kelistrikan dan mengurangi konsumsi bahan bakar minyak di daerah terpencil. PLN yang bertanggung jawab dalam meningkatkan rasio kelistrikan memerlukan standard teknis yang dapat digunakan oleh kantor wilayah dalam merencanakan dan membangun PLTS. Pada makalah ini dibahas konfigurasi dasar PLTS, spesifikasi teknis peralatan utama seperti modul surya, inverter dan baterai serta pertimbangan dalam menentukan kapasitas PLTS. Kata kunci: energy surya, fotovoltaik, konfigurasi dasar